(3UfGYI GdSjGMI (B/s - (3Jhajb , eGgQ YHO GdYRjRs ((3YeGf(B: s (3OGQ RgQf ddfTQ(B, s, 2008)
(3fTCI h JWhQ GdSjGMI h GdJWQb Gdi GdSjGMI h GdSGFM h GgejI GdSjGMI h GQJHGW fTGWGJ GdSjGMI h CQcGfgG eY JfGhd OhGaY GdSaQ h CfhGY GdSjGMI h cPG GdSjGMI UfGYI eQcHI h YdGbI GdSjGMI HGdYdhe GdGNQi h UfGYI GdSjGMI h YdGbJgG HUfGYI GdafGOb h HUfGYI Gdfbd h cPG GdGMUGA GdSjGMj h GdJShjb GdSjGMj h JfGhd hcjd GdSaQ h GdTQcGJ GdSjGMjI h GdefXeGJ GdYGdejI GdJj JYfi HTDhf GdSjGMI hhSGFd GdfghV HGdSjGMI h CNjQG GdUMI h GdSaQ(B.s
(3edGMb U(B.243 (3eQGLY U(B.250 (3eUWdMGJ SjGMjI U(B.221s
Keywords: (3GdSjGMIs